2019
DOI: 10.1002/chem.201900173
|View full text |Cite
|
Sign up to set email alerts
|

Topotactic Conversion of Alkali‐Treated Intergrown Germanosilicate CIT‐13 into Single‐Crystalline ECNU‐21 Zeolite as Shape‐Selective Catalyst for Ethylene Oxide Hydration

Abstract: The conversion of the alkali‐treated intergrowth germanosilicate CIT‐13 into the single‐crystalline high‐silica ECNU‐21 (named after East China Normal University) zeolite, with a novel topology and a highly crystalline zeolite framework, has been realized through a creative top‐down strategy involving a mild alkaline‐induced multistep process consisting of structural degradation and reconstruction. Instead of acid treatment, hydrolysis in aqueous ammonia solution not only readily cleaved the chemically weak Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 43 publications
1
66
0
Order By: Relevance
“…As an important type of zeolites, germanosilicatebased zeolites provide many new structures, exhibiting excellent performance in various catalytic reactions. [23][24][25][26][27][28][29][30][31][32][33][34] For example, BEC zeolite displays good catalytic performance in the isomerization of glucose to fructose; [24] ECNU-21 zeolite is an efficient shape selective catalyst for ethylene oxide hydration; [25] ITH zeolite shows excellent performance in the catalytic cracking and methanol-to-propylene (MTP) reaction. [26][27][28][29] ITH zeolite, firstly discovered by Cormas group, [30] has a special framework structure (three dimensional 9 10 10membered ring channels; aperture size of 4.0 4.8, 4.8 5.1, and 4.8 5.3 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an important type of zeolites, germanosilicatebased zeolites provide many new structures, exhibiting excellent performance in various catalytic reactions. [23][24][25][26][27][28][29][30][31][32][33][34] For example, BEC zeolite displays good catalytic performance in the isomerization of glucose to fructose; [24] ECNU-21 zeolite is an efficient shape selective catalyst for ethylene oxide hydration; [25] ITH zeolite shows excellent performance in the catalytic cracking and methanol-to-propylene (MTP) reaction. [26][27][28][29] ITH zeolite, firstly discovered by Cormas group, [30] has a special framework structure (three dimensional 9 10 10membered ring channels; aperture size of 4.0 4.8, 4.8 5.1, and 4.8 5.3 ).…”
Section: Introductionmentioning
confidence: 99%
“…UTL)a nd its derivative, which contain only oxygen bridges as interlayer connecting units (PCR,F igure 1). [62] Other techniques,s uch as "inverse sigma transformation" [31] or "topotactic conversion", [63] recently applied to germanosilicates,a re based on similar principles and individual steps.…”
Section: Synthesis Of New Zeolite Structuresmentioning
confidence: 99%
“…More detailed characterization indicated that the presence of Si▬O▬Si bonds vertical to the Si-rich layers may prohibit the successful selective removal of D4R subunits [64]. Wu et al reported a mild alkaline treatment to hydrolyze both Ge▬O▬Ge(Si) and Si▬O▬Si bonds in the D4R subunits, giving a layered intermediate ECNU-21P (Figure 5), which was transformed to 3D ECNU-21 zeolite upon calcination [26]. In addition, the selective removal of D4R subunits from CIT-13 zeolite eliminates the intergrowth phenomena and resulted in a single crystalline zeolite framework.…”
Section: Synthesis Of Layered Zeolites By Selective Removal Of Doublementioning
confidence: 99%